Electrocatalytic detection of ascorbic acid using N,N,N’,N’-tetramethyl-para-phenylene-diamine (TMPD) mediated oxidation at unmodified gold electrodes; reaction mechanism and analytical application - Kuss, S; Compton, R (Elsevier, 2017)
The redox mediator N,N,N’,N’-tetramethyl-para-phenylene-diamine (TMPD) is shown to catalyse oxidation of ascorbic acid (AA), which is otherwise known to exhibit irreversible electrode kinetics and produce deposits on the electrode surface. The mechanism of the catalysed reaction is reported and inferred to follow the sequence TMPD − e− ⇄ TMPD+* TMPD+* + AA ⇄ TMPD + AA+* AA+* + AA+* → AA + products AA+* + AA+* → AA + AA2+ Kinetic parameters are deduced from the modelling of cyclic voltammetry as a function of voltage scan rate. Using TMPD, AA can be oxidized at a low overpotential where direct electrochemical oxidation is minimal, and products are formed in solution. Consequently, electrode fouling is avoided and a reliable electrochemical signal can be recorded on unmodified gold electrodes, allowing the quantitative analysis of AA in even complex media without pre-treatment of the samples. The presented method offers high sensitivity, with a sufficient limit of detection for the detection of AA in beverages, without interferences from others reactants during cyclic voltammetry measurements. The applicability of the technique is demonstrated on commercial orange juice, offering a straight forward, inexpensive and precise alternative to other AA determination strategies.